2016
DOI: 10.3823/1920
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Major Depression And Type 2 Diabetes Mellitus: A Meta-Analysis And Meta-Regression Of Observational Studies

Abstract: The purpose of this review was to identify the prevalence of major depression in individuals with type 2 diabetes by means of a systematic review and meta-analysis. An electronic search was conducted for relevant studies published from January 1988 to December 2014. Cross-sectional and case-control studies in adults that evaluated the prevalence of major depression in individuals with type 2 Diabetes Mellitus were included. Meta-regression and sensitivity analyses were used to identify the sources of heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…Although Lin et al [ 8 ] in 2008 agreed with the finding that the risk of depression was slightly higher among diabetes patients than among patients without diabetes (ageand sex-adjusted OR, 1.38; 95% CI, 1.15–1.66), they reported that OR estimates between countries were not significantly different (P=0.54). This finding was supported by a recent meta-analysis of studies conducted in Europe, Asia, and the Americas by Lopes et al [ 9 ] in 2016. In this analysis, the prevalence of depression among patients with T2DM was higher than among nondiabetic individuals, independent of the geographic location (OR, 2.06; 95% CI, 1.13–3.74; P=0.0174).…”
Section: Prevalence and Risk Of Depression Among Diabetes Patientssupporting
confidence: 64%
“…Although Lin et al [ 8 ] in 2008 agreed with the finding that the risk of depression was slightly higher among diabetes patients than among patients without diabetes (ageand sex-adjusted OR, 1.38; 95% CI, 1.15–1.66), they reported that OR estimates between countries were not significantly different (P=0.54). This finding was supported by a recent meta-analysis of studies conducted in Europe, Asia, and the Americas by Lopes et al [ 9 ] in 2016. In this analysis, the prevalence of depression among patients with T2DM was higher than among nondiabetic individuals, independent of the geographic location (OR, 2.06; 95% CI, 1.13–3.74; P=0.0174).…”
Section: Prevalence and Risk Of Depression Among Diabetes Patientssupporting
confidence: 64%
“…4,5 There is evidence that the prevalence of depression is moderately increased in prediabetic patients and in undiagnosed diabetic patients, and markedly increased in the previously diagnosed diabetic patients compared to normal glucose metabolism individuals. 6,7 Different environmental factors (epigenetic factors) may activate common pathways that promote DM2 and depression in the end. 8 One of the important factors are low socioeconomic status, poor sleep, lack of physical exercises and diet.…”
mentioning
confidence: 99%